Case Report: Loss-of-Function ABCC9 Genetic Variant Associated With Ventricular Fibrillation - Zaytseva, Anastasia; Tulintseva, Tatyana; Fomicheva, Yulya; Mikhailova, Valeria; Treshkur, Tatiana; Kostareva, Anna (Frontiers in Genetics, 2022)
Genetic variants in the ABCC9 gene, encoding the SUR2 auxiliary subunit from KATP channels, were previously linked with various inherited diseases. This wide range of congenital disorders includes multisystem and cardiovascular pathologies. The gain-of-function mutations result in Cantu syndrome, acromegaloid facial appearance, hypertrichosis, and acromegaloid facial features. The loss-of-function mutations in the ABCC9 gene were associated with the Brugada syndrome, early repolarization syndrome, and dilated cardiomyopathy. Here, we reported a patient with a loss-of-function variant in the ABCC9 gene, identified by target high-throughput sequencing. The female proband presented with several episodes of ventricular fibrillation and hypokalemia upon emotional stress. This case sheds light on the consequences of KATP channel dysfunction in the cardiovascular system and underlines the complexity of the clinical presentation of ABCC9-related diseases.